2018
DOI: 10.12716/1001.12.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Dredging Volumes Prediction for the Access Channel of Santos Port Considering Different Design Depths

Abstract: Santos is the most important Brazilian port, handling about 114 million of tons in 2016. In 2010, there was a great capital dredging in order to deepen the Access Channel to 15m deep (Chart Datum-CD). This depth was not achieved, due to inefficiency on dredging procedures. As deepening and maintaining design depths are indispensable, this study presents an analysis of sediment deposition in Santos Port Access Channel and an annual dredging volumes prediction, considering current bathymetric survey and design d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…As described in Pion and Bernardino [3], the port of Santos is situated on the south eastern coast of Brazil, as depicted in Figure 1. The city of Santos is located on Sao Vicente Island, within a highly intricate estuarine system with over 60 river outfalls.…”
Section: Study Area Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Pion and Bernardino [3], the port of Santos is situated on the south eastern coast of Brazil, as depicted in Figure 1. The city of Santos is located on Sao Vicente Island, within a highly intricate estuarine system with over 60 river outfalls.…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…In a scenario of increasing ship dimensions worldwide, associated with the role of the Port of Santos as a hub port, it is estimated that, soon, it will be necessary to implement a new design depth to serve new vessels. Pion and Bernardino [3] indicated that there is an increase in the maintenance dredging volumes required to maintain greater depths in the access channel. For the maintenance of the condition presented by the bathymetric survey of 2016, a maintenance dredging of approximately 4,325,000 m³ per year would be necessary, increasing to approximately 5,000,000 m³, 6,700,000 m³ and 7,900,000 m³ considering depths of 15 m, 16 m and 17 m, respectively, for the Access Channel to the Port of Santos.…”
Section: Introductionmentioning
confidence: 99%
“…Those with the highest buoyancy (plastics, Styrofoam and wood) were distributed along the beach, while less floating material debris (foam, paper, fabric and nylon) concentrated in the deposition zone, where there is low ocean-circulation due to the construction of the emissary near Urubuqueçaba Island. The T3 transect was recorded as an entry of marine planktonic organisms (cnidarian) that originate from the open sea and are transported by surface currents to the beach (Alfredini et al 2008, Pion, Bernardino 2018.…”
Section: Heavy Debrismentioning
confidence: 99%
“…The bathymetric surveys belong to the family of hydrographic surveys and are carried out whenever there is a need to precisely know the morphological trend of the seabed [4], [5]. They are therefore preliminary to the realization of maritime and river works and in the case of works already supplied, they are indispensable to verify continuously water heads and dredging volumes [6].…”
Section: Introductionmentioning
confidence: 99%